Penilaian Tingkat Kematangan Keselarasan Strategi Bisnis Dan TI Menggunakan Luftman Maturity Model (Kasus : Unika Soegijapranata) - F X Hendra Prasetya; Bernardinus Harnadi; Agus Cahyo Nugroho (Politeknik Harapan Bersama, 2020)
ITGI (IT Governance Institute) states that the alignment of business strategy and IT organization is the key to realizing the benefits of IT for business. The large gap / gap between IT strategy and business strategy will have an impact on the organization's business performance, especially if the organization relies on IT in its business operations or making IT as one of its selling points. Unika Soegijapranata as one of the tertiary institutions sees IT as a mandatory requirement to build competence and capability in the context of competition in its area. The purpose of this study is to assess the alignment level of business and IT strategies at Soegijapranata Unika by using the Luftman SAMM (Strategic Alignment Maturity Model) model. This study uses data collection methods through questionnaires and interviews with University leaders and University IT Institution Leaders. Currently Unika Soegijapranata has a strategic alignment value that is at level 4 (Improved / Managed Process), where at level 4 institutions are said to have focused on investing in IT to win the competition.